Perlindungan Pasien Atas Tindakan Malprakter Dokter - Muhammad Afzal (Lembaga Penelitian dan Pendidikan Mandala, 2017)
One of the causes of malpractice is a mistake whose shape is intentional and negligence in criminal law. So that in case of actions carried out by doctors and patients more menenderita result of the disease initially, disability, and even death, then it is categorized as a medical malpractice that may be subject to criminal. But if we look at the malpractice of a legal point of view, it is difficult to find the point of balance and fairness objective for both sides both and physicians as a victim itself. A responsibility will arise after the legal act occurred, which is basically the responsibility aims to make something bad into balance by doing something else instead. In particular criminal act of malpractice itself would be difficult to give a rational accountability for actions carried out, but public law gives space to the forced power in it to give an account as well the protection of victims and private law will provide space for compensation for actions that harm the other person, which includes how much compensation costs incurred during the treatment and after the occurrence of malpractice. In addition there is also immaterial damages that are difficult to determine where the nominal amount as losses related to mental and psychic victim, so it needs a better approach to form emotional relationships that are the responsibility and protection